Eksistensi Bahasa kokoda dan dialek bahasa indonesia masyarakat kokoda dalam pelestarian identitas - yusria, asna naila; Gledis Miseri; Abdul Mufid Maelan; Riyanti; Fauzan Adnan Dzaki Mubarak (El-Tarbawi : Jurnal Pendidikan Islam dan Humaniora, 2026)
Urbanization drives massive shifts in local languages across various regions of Indonesia. This study examines the dynamics of language preservation within the Kokoda tribal community in Warmon Village, Sorong Regency. The researcher focus on three main objectives. First, the researcher analyze the current survival of the native Kokoda language. Second, the researcher map the distinctive pronunciation characteristics of the Indonesian dialect spoken by Kokoda people. Third, the researcher investigate the role of these language variations in maintaining their cultural identity. This study applies a qualitative sociolinguistic approach with a descriptive method. The researcher gathered field data through in-depth interviews with cross-generational informants and direct participant observations. The results show a significant decline in active regional language skills among Kokoda youth. Most of the younger generation only possess passive comprehension due to limited daily conversational space outside the home. Interestingly, the community compensates for this decline by creating a unique hybrid Indonesian dialect. This dialect features a heavy accent and blends native Kokoda vocabulary into Indonesian sentences. From a sociolinguistic perspective, this hybrid dialect serves as a tool for solidarity and social boundary marking. The researcher recommend strengthening the transmission of the mother tongue in the family domain to prevent the total loss of the local language. Keywords: language existence, Kokoda dialect, sociolinguistics, language maintenance, cultural identity.